Effect of prednisolone and cetirizine on D. farinae and histamine-induced wheal and flare response in healthy dogs - Temizel, E. M.; Cihan, H.; Akhtardanesh, B.; Aytug, N. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2011)
Objective: Prednisolone and antihistamines are highly potent drugs in the treatment of atopic dermatitis and widely used in humans and dogs. In some atopic patients in which antihistamines, corticosteroids or other drugs have already been administered intradermal testing (IDT) may be necessary. The aim of the present study was to compare the effects of cetirizine and prednisolone on IDT results. Material and methods: Thirty healthy dogs (average age 5.9 ± 0.6 years) were randomly assigned to three groups. Treatment groups were administered prednisolone (1 mg/kg BW daily, tapering dosage; group I), cetirizine (1 mg/kg BW daily; group II) and placebo (group III) respectively for one week. In the second week, none of the dogs received any medications. IDT was performed prior to drug administration and results obtained were considered as the baseline response. Second and third IDTs were performed at the end of the first and second week, respectively. Results: In groups I and II IDT reactivity was reduced at the end of first week (p < 0.05). After drug discontinuation the reactivity almost returned to baseline at the end of the 2-week period, with the exception of the prednisolone group for D. farinae. Conclusion: Prednisolone and cetirizine have significant effects on IDT reactions and must be withdrawn by veterinary practitioners up to 2 weeks prior to IDT.
Keywords: Intradermal testing; atopia; antihistamines; canine